An Alternative Approach to Prescribing Sternal Precautions After Median Sternotomy, "Keep Your Move in the Tube". Issue 1 (1st January 2016) - Adams, Jenny; Lotshaw, Ana; Exum, Emelia; Campbell, Mark; Spranger, Cathy B.; Beveridge, Jim; Baker, Shawn; Mccray, Stephanie; Bilbrey, Tim; Shock, Tiffany; Lawrence, Anne; Hamman, Baron L.; et al.
Abstract : Traditional sternal precautions, given to sternotomy patients as part of their discharge education, are intended to help prevent sternal wound complications. They vary widely but generally include arbitrary load and time restrictions (lifting no more than a specified weight for up to 12 weeks) and may prohibit common shoulder joint and shoulder girdle movements. Having observed the negative effects of restrictive sternal precautions for many years, our research team performed a series of studies that measured the forces exerted during various common activities and their relationship to the sternum. The results, though informative, led us to realize that the goal of identifying "the" appropriate load restriction to prescribe for sternotomy patients was futile. The alternative approach that we introduce applies standard kinesiological principles and teaches patients how to perform load-bearing movements in a way that avoids excessive stress to the sternum.